2006
DOI: 10.1677/joe.1.06310
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin enhances glucose-induced insulin secretion in scheduled meal-fed sheep

Abstract: The purpose of this study was to investigate the effects of physiologic levels of ghrelin on insulin secretion and insulin sensitivity (glucose disposal) in scheduled fedsheep, using the hyperglycemic clamp and hyperinsulinemic euglycemic clamp respectively. Twelve castrated Suffolk rams (69·8 0·6 kg) were conditioned to be fed alfalfa hay cubes (2% of body weight) once a day. Three hours after the feeding, synthetic ovine ghrelin was intravenously administered to the animals at a rate of 0·025 and 0·05 µg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 28 publications
2
43
1
2
Order By: Relevance
“…This was not surprising as insulin is released in response to nutrient intake (Takahashi et al, 2006). Because these animals were not subjected to nutrient restriction they would have been secreting insulin at a higher rate to accommodate the rise in blood glucose and to promote protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This was not surprising as insulin is released in response to nutrient intake (Takahashi et al, 2006). Because these animals were not subjected to nutrient restriction they would have been secreting insulin at a higher rate to accommodate the rise in blood glucose and to promote protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, ghrelin, which is released mainly from the oxyntic gland of the stomach with a transient surge just before feeding and stimulates GH secretion in rodents and ruminants [37], attenuates the capacity of insulin to suppress endogenous glucose production but reinforces that which stimulates glucose disposal, when it is infused for 3 h [38]. However, the steady-state glucose infusion rate was unaffected by ghrelin infusion in a hyperinsulinemic euglycemic clamp experiment in sheep [39]. It may be necessary to investigate whether a transient surge just before feeding in ghrelin produces a change in insulin sensitivity for glucose utilization rate in ruminants, in order to elucidate a mechanism for producing the feeding-induced increase in the rate.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that plasma levels of ghrelin were inversely related with those of insulin around feeding in sheep (unpublished data). Furthermore, we have demonstrated that ghrelin infusion stimulates glucose-induced insulin secretion in meal-fed sheep (Takahashi et al 2006). These observations led us to hypothesize that ghrelin regulates insulin secretion dependent on energy balance.…”
Section: Introductionmentioning
confidence: 85%
“…Insulin Insulin assay was done as described previously (Takahashi et al 2006). The insulin concentration was measured by competitive solid-phase immunoassay using Europium (Eu)-labeled synthetic bovine insulin and polystyrene microtiter strips (Nalge Nunc Int.)…”
Section: Hyperglycemic Clampmentioning
confidence: 99%